Vulnerability to Climate Change in Agricultural Systems in Latin America and the Caribbean : Building Response Strategies - World Bank (Washington, DC, 2016)
This study reports the results of “action research” to identify and prioritize stakeholder driven, locally relevant response options to climate change. These response options comprise the basis of local action plans developed to address agricultural adaptations to climate change in three diverse agroecoystems: the Yaqui Valley in northwestern Mexico, the Mantaro Valley in central Peru, and the western littoral regional of Uruguay. The study has three primary objectives. The first is to develop and apply a pilot methodology for assessing agricultural vulnerability to climate change and for formulating response strategies to inform private and public sector decisions in the Latin America region. The second objective is to formulate recommendations for investments in each of the selected agro-ecosystems in a range of areas including agricultural technology adaptation, infrastructure investments, public and private sectoral support activities, and institutional and policy changes. The final objective is to disseminate the study results in the Latin America region to help increase understanding of the impacts of climate change and alternative adaptation response strategies.